Chemodiversity of Galactans from Different Red Seaweed Species with Emphasis on their Antioxidant and Antiproliferative Activities in vitro - Ismail,Mona Mohamed (2022)
Abstract Crude galactans isolated from five different seaweed species collected from the Lebanese coast were chemically characterized and then evaluated for their antioxidant and antiproliferative properties in vitro. The yield of extracted sulfated galactans varied in the range 4.03%-14.32% dry weight in Tricleocarpa fragilis and Osmande dechybrida, respectively. The chemical composition of all extracted galactans exhibited high levels of carbohydrate, uronic acid and sulfate contents with trace amounts of protein. FTIR analysis showed that all the extracted galactans were agar except for Galaxaulra rugosa galactan (GRG) and O. dechybrida galactan (ODG). The antioxidant activity of all extracted galactans using multifunctional antioxidant ability was assayed by total antioxidant capacity, DPPH radical-scavenging activity, hydrogen peroxide scavenging assay and reducing power. Galactans from G. rugosa exhibited higher antioxidant activity compared with the standard antioxidant (α-tocopherol). Whereas T. fragilis galactan (TFG) showed the lowest antioxidant activity. The maximum antiproliferative potency was detected in GRG and Ligora viscida galactan (LVG) at 1.5%. The tested biological activity of the isolated galactans increased with increasing concentrations, indicating the dose-dependency of their chemical properties. The antiproliferative activity showed a significant positive correlation with antioxidant activities. Moreover, these activities were correlated with the combined effects of uronic acid and sulfate content. Identification of these sulfated polysaccharides in algal species is chemotaxonomic significance in view of their potential economical applications as a natural product. The most activated galactans have been selected for further fractionation and characterization and the necessary in vivo experiments are already in progress.